2015
DOI: 10.1186/s12893-015-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Perineal pseudocontinent colostomy is safe and efficient technique for perineal reconstruction after abdominoperineal resection for rectal adenocarcinoma

Abstract: BackgroundThe aim of this study was to evaluate oncologic results and satisfaction rate results of pseudocontinent perineal colostomy (PCPC) using Schmidt’s technique in patients undergoing abdominoperineal resection (APR) for managing low rectal adenocarcinoma.MethodsFrom January 1993 and December 2007, One hundred and forty six patients underwent successfully PCPC after abdominoperineal resection for lower rectal adenocarcinoma. There were 75 women, with an average age of 47 years old. All patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…The main oncological advantage of PPCC technique is to allow early diagnosis of pelvic recurrences by rectal examination or by echo-endoscopy [7,9], like in our case, the local recurrence was identified by clinical rectal inspection and confirmed by histological findings before adequate treatment was initiated.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The main oncological advantage of PPCC technique is to allow early diagnosis of pelvic recurrences by rectal examination or by echo-endoscopy [7,9], like in our case, the local recurrence was identified by clinical rectal inspection and confirmed by histological findings before adequate treatment was initiated.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, Kuzu et al [8] mentioned that social, physical, sexual, and psychological aspects of life, in addition to religious worship, are severely impaired by sphincter sacrificing surgery in the Islamic population. As an alternative Skouda et al [9] demonstrated that PCPC provides a high degree of patient satisfaction without compromising oncological results. It is a good option in selected patients, especially in Muslim countries.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of mucosal prolapse with perineal colostomy is 0-21% in eight reports that include 14-146 patients. [1][2][3][4][5][6][7][8] Simple mucosal resection under local anaesthesia appears effective in this situation. To the best of our knowledge, fullthickness perineal colostomy prolapse has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] This major complication ranges from partial and occasional to total incontinence, with increased frequency and urgency, or constipation and incomplete emptying, all encompassed in the low anterior resection syndrome (LARS). [4,5] This syndrome is associated with a negative impact on the quality of life, [6] and is subject to a multitude of assessment tools most of which incorporate the same parameters, including the nature of incontinence ( atus, liquid seepage, liquid incontinence, solid incontinence), the incontinence type (active awareness, passive non-awareness, urge incontinence), the quantity of loss, the frequency of incontinence episodes, and accompanying complaints such as abdominal/pelvic pain and obstructed defecation. Among these assessment methods, the low anterior resection syndrome score ( LARS score) has been speci cally elaborated to explore the low anterior resection syndrome in patients after curative rectal surgery [7] .…”
Section: Introductionmentioning
confidence: 99%